Preliminary Studies of Two-Phase Effects on Pressure Transient Data - Cox, B. Lee; Bodvarsson, Gudmundur S. (Lawrence Berkeley National Laboratory, 1986)
Presently, there are few methods available for analyzing pressure transient data from two-phase reservoirs. Methods published in the oil and gas literature (Earlougher, 1977) have been adapted for analyzing data from geothermal reservoirs, assuming a uniform initial steam saturation. However, it is well known that two-phase conditions often prevail only in parts of the reservoir, primarily in the top portion, and that vapor saturations are not uniform. Thus, there is a need to examine the pressure behavior during well tests considering more realistic conditions. Two-phase effects are important in pressure transient analysis because the mobility of two-phase mixtures can differ significantly from that of single-phase fluids. Also, the compressibility of two-phase mixtures is orders of magnitude higher than for single-phase liquid and vapor (Grant and Sorey, 1979). In this paper we perform scoping calculations on the effects of two-phase zones on well pressure transients. Three different cases are considered (Figure 1). The first is that of a fully two-phase system (e.g. Krafla, Iceland; Stefansson, 1981). This problem has been studied by various authors, including Moench and Atkinson (1977, 1978), Grant (1978), Garg (1978, 1980), Grant and Sorey (1979), and Aydelotte (1980). Some of the complexities of this type of system are discussed. The second problem is that of a single-phase liquid reservoir with a localized two-phase zone. Possible field examples include Cerro Prieto, Mexico and Baca, New Mexico, USA. This problem was studied by Sageev and Horne (1983a,b) and Sageev (1985); they used a constant pressure approximation for the two-phase zone. In this paper we investigate the pressure transients in a well located near an isolated two-phase zone in a single-phase liquid reservoir, and compare them to type curves based upon the constant pressure approximation. The third problem considered is that of a two-phase layer overlying a single-phase liquid layer. One example of such a reservoir is the Svartsengi geothermal field in Iceland (Gudmundsson e t al., 1985). Little research has been done on pressure transients in such systems. The numerical code MULKOM (Pruess, 1983) is used to simulate the three cases.